Tourism Expansion and Area-Based Balance in Thailand - Chaivichayachat, Bundit (Business Administration and Management Journal Review, 2023)
Tourism sector in Thailand has been expanded over the past decade both in term of demand for Thai tourism and tourism revenues. However, the expansion has been concentrated only in Bangkok and first-tier tourism cities. Then, this paper aim to evaluate the area-based balance in the period of tourism expansion (2009 to 2018) by employed Gini coefficient. The results indicate the high degree of imbalances in area-based basis especially for the case of foreign visitors. According to the finding, the recommendations are (1) the promotion for the expenditure per trip, (2) the enhancing for the linkage to non-related tourism sectors, and (3) the integrating of tourism components in second-tier tourism cities.